AMBLIOPIA BILATERAL DISERTAI EKSOTROPIA ALTERNANS DAN ASTIGMATISMA MIOPIA KOMPOSITUS - Tumewu, Sigmund I. E. (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: Amblyopia is a functional disorder of vision without any organic problem, and consists of four types: strabistic, anisometropic, ametropic, and stimulus deprivation. The most common type is strabistic amblyopia. Generally, this disorder occurs in children but their parents do not realize it until their children complain of blurred vision during their activities at school. We reported a male of 12 years old who came to the hospital with a cross-eyed chief complaint. This disorder had been realized by his parents since he was six years old. The eye crossing was permanent, not intermittent, but alternating between his two eyes. Examination performed was visual acuity with a cycloplegic refraction, autorefraction, streak retinoscopy, prism, and cover test for evaluating the eye deviation. Conclusion: Based on all the tests performed, the diagnosis of this patient was bilateral amblyopia accompanied with alternant exotropia and myopic astigmatism. The management of this patient was to correct the refraction disorder with cycloplegic refraction and alternant patching. Keywords: amblyopia, exotropia, astigmatism. Abstrak: Ambliopia adalah suatu kelainan fungsional dari penglihatan tanpa disertai kelainan organik, dan terbagi atas empat tipe yaitu; strabismus, anisometropik, ametropik, dan deprivasi stimulus. Bentuk yang paling sering ditemukan ialah tipe strabismus. Umumnya gangguan ini terjadi pada anak-anak tanpa disadari orang tua dan terdeksi pada saat mengikuti pendidikan di sekolah dengan manifestasi turunnya tajam penglihatan. Kami melaporkan kasus seorang anak laki-laki berusia 12 tahun yang berobat ke Poliklinik Ilmu Kesehatan Mata RSU Prof. Dr. R.D. Kandou Manado dengan keluhan mata juling. Mata juling disadari orang tua sejak pasien berusia enam tahun (kelas 1 SD). Juling bersifat menetap tidak hilang timbul, tetapi terjadi bergantian mata kiri dan kanan. Pemeriksaan yang dilakukan meliputi pemeriksaan tajam penglihatan (visus) dengan sikloplegik, autorefraksi, streak retinoscopy, pemeriksaan cover test, dan prisma untuk menilai adanya deviasi mata ambliopia. Simpulan: Berdasarkan hasil pemeriksaan yang dilakukan, diagnosis pasien ini ialah ambliopia bilateral disertai eksotropia alternans dan astigmatisma miopia kompositus. Penanganan pasien dilakukan dengan koreksi refraksi sikloplegik dan alternant patching. Kata kunci: ambliopia, eksotropia, astigmatisma.